LC-MS based stability-indicating method for studying the degradation of lonidamine under physical and chemical stress conditions - Ankit Kanaiyalal Rochani; Margaret Wheatley; Brian Edward Oeffinger; John Robert Eisenbrey; Gagan Kaushal (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: Lonidamine is a hexokinase II inhibitor, works as an anticancer molecule, and is extensively explored in clinical trials. Limited information prevails about the stability-indicating methods which could determine the forced degradation of lonidamine under stressed conditions. Hence, we report the use of a rapid, sensitive, reproducible, and highly accurate liquid chromatography and mass spectrometry method to analyze lonidamine degradation. Experimental approach: The Xbridge BEH shield reverse phase C18 column (2.5 μm, 4.6 × 75 mm) using isocratic 50:50 water: acetonitrile with 0.1% formic acid can detect lonidamine with help of mass spectrometer in tandem with an ultraviolet (UV) detector at 260 nm wavelength. Findings/ Results: A linear curve with r2 > 0.99 was obtained for tandem liquid chromatography-mass spectrometry (LC-MS)-UV based detections. This study demonstrated (in the present set up of isocratic elution) that LC-MS based detection has a relatively high sensitivity (S/N (10 ng/mL): 220 and S/N (20 ng/mL): 945) and accuracy at lower detection and quantitation levels, respectively. In addition to developing the LC-MS method, we also report that the current method is stability-indicating and shows that lonidamine gets degraded over time under all three stress conditions; acidic, basic, and oxidative. Conclusion and implications: LC-MS based quantitation of lonidamine proved to be a better method compared to high-performance liquid chromatography (HPLC)-UV detections for mapping lonidamine degradation. This is the first report on the stability-indicating method for studying the forced degradation of lonidamine using LC-MS method.